Video-stimulated recall by video and the performative perception of chemistry teachers about didactic sequences and the learning evaluation (Revista Contexto & Educação, 2025)
This article addresses the perception of performance and episodic reflection of two chemistry teachers regarding evaluation, based on their memories stimulated by video-stimulated scenes. Guided by the research question “What are the students' conceptions of evaluation in the context of applying two problem-based sociocientific teaching sequences?”, the aim of this research focus is to understand their conceptions of learning evaluation within the context of applying two sociocientific problem-oriented teaching sequences. The methodology involved the use of stimulated recall to analyze how the two chemistry teachers developed meanings about the context of applying teaching sequences and evaluation learning. Audio and video recordings of the lessons were made, followed by interviews with the teachers. The data were analyzed using NVivo 12® software, employing automatic coding and categorical analysis of the responses, with a focus on evaluation conceptions. The results of this study lead to the conclusion that the teachers engaged in a reflective process about their actions in the stimulated recall, an activity that created meaningful contexts for argumentation, performative interpretation, and the analysis of teaching episodes. The conceptions of evaluation reveal different approaches to developing it within the teaching sequences, highlighting the emergence of tensions, dilemmas, and contradictions due to institutional demands and challenges in teaching chemistry.
Keywords: Evaluation; didactic sequences; science teaching; performance